Genetic analysis of the frozen microbiome at 7900 m a.s.l., on the South Col of Sagarmatha (Mount Everest). Issue 1 (31st December 2023) - Dragone, Nicholas B.; Perry, L. Baker; Solon, Adam J.; Seimon, Anton; Seimon, Tracie A.; Schmidt, Steven K.
ABSTRACT: Microbial communities in alpine environments >7, 500 m.a.s.l. have not been well studied using modern cultivation-independent sequencing approaches due to the challenges and danger associated with reaching such high elevations. For this reason, we know little about the microorganisms found in sediments on Earth's tallest mountains, how they reach these surfaces, and how they survive and remain active at such extreme elevations. Here, we explore the microbial diversity recovered from three sediment samples collected from the South Col ( 7, 900 m.a.s.l.) of Sagarmatha (Mount Everest) using both culturing and next generation sequencing approaches (16S rRNA gene, internal transcribed spacer [ITS] region, and 18S rRNA gene sequencing). Both approaches detected very low diversity of bacteria, protists, and fungi that included a combination of cosmopolitan taxa and specialized microorganisms often found at high elevations like those of the genera Modestobacter and Naganishia . Though we managed to grow viable cultures of many of these taxa, it remains likely that few, if any, can be active in situ at the South Col. Instead, these high-elevation surfaces may act as deep-freeze collection zones of organisms deposited from the atmosphere or left by climbers scaling the Earth's highest mountain.